Urban Transport Expansions and Changes in the Spatial Structure of U.S. Cities: Implications for Productivity and Welfare - Baum-Snow, Nathaniel (The Review of Economics and Statistics, 2020)
Each new radial highway serving large U.S. metropolitan areas decentralized 14% to 16% of central city working residents and 4% to 6% of jobs in the 1960–2000 period. Model calibrations yield implied elasticities of central city total factor productivity to central city employment relative to suburban employment of 0.04 to 0.09, meaning a large fraction of agglomeration economies operates at submetropolitan-area spatial scales. Each additional highway causes central city income net of commuting costs to increase by up to 2.4% and housing cost to decline by up to 1.3%. Factor reallocation toward land in housing production generates the plurality of the population decentralization caused by new highways.